Preliminary study in discovering 2-propen-1-one, 1-(2,4-dihydroxyphenyl)-3-(4-methoxyphenyl)- from syzygium aqueum leaves as a tyrosinase inhibitor in food product: experimental and theoretical approach - Zarudin, Nurul Husna; Abdullah, Erna Normaya; Yunus, Kamaruzzaman; Ku Bulat, Ku Halim; Ahmad, Mohammad Norazmi (2019)
In this study, response surface methodology (RSM) in combination with central composite rotatable design (CCRD) were performed to optimize the extraction parameters for total phenolic content (TPC) on Syzygium aqueum (S. aqueum) leaves. The effect of operational conditions on the extraction of S. aqueum leaves using carbon dioxide (CO2) on TPC was investigated. The conditions used in the supercritical extraction with CO2 included temperatures of (40-70 °C), pressures (2200-4500 psi) and extraction time (40-100 min). The highest TPC (3.5893 mg GAE/mg) was obtained at optimum conditions of 55 °C, 3350 psi and 70 min. The major compound in the optimized crude extract was2-propen-1-one,1-(2,4Dihydroxyphenyl)-3-(4-methoxyphenyl)- (82.65 %) which was identified by GC-MS. COSMO-RS was introduced to study the σ-profile between CO2 and 2-propen-1-one,1-(2,4-Dihydroxyphenyl)-3-(4methoxyphenyl)-. Principal component analysis (PCA) was performed to classify major compound which exhibit similar chemical properties with selected control. 2-propen-1-one,1-(2,4-Dihydroxyphenyl)-3-(4methoxyphenyl)- has similar chemical properties with kaempferol as tyrosinase inhibitor. Molecular electrostatic potential (MEP) and molecular docking were plotted to investigate a recognition manner of 2-propen-1-one,1-(2,4-Dihydroxyphenyl)-3-(4-methoxyphenyl)-upon tyrosinase receptor.